Optimalisasi Pengembangan UMKM Melalui Legalitas Usaha dan Branding Media Sosial di Kelurahan Wonokusumo - Istiqomah Agustin; Astrini Aning Widoretno (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This research aims to analyze the optimization of business legality development and social media branding in Wonokusumo Village. This type of research uses a qualitative method, which combines interviews, observation, and documentation of Wonokusumo Village MSMEs. The results showed that business legality and social media branding are still not optimal among Wonokusumo MSMEs. The results of this study reveal that there are still many MSMEs that do not know the purpose, objectives and benefits of business legality. They tend to put aside business licensing matters and prefer to focus on the sales results of their business alone. Likewise, with the understanding and use of social media branding, many of the business actors still do not use social media branding due to limited quality of human resources.